2010
DOI: 10.1021/jf9030635
|View full text |Cite
|
Sign up to set email alerts
|

Berry Ellagitannins May Not Be Sufficient for Prevention of Tumors in the Rodent Esophagus

Abstract: Biodirected fractionation is used to identify the active inhibitory constituents in berries for esophageal cancer in rats. The present study was undertaken to determine if ellagitannins contribute to the chemopreventive activity of an alcohol/water-insoluble (residue) fraction of berries. Rats consumed diets containing residue fractions of three berry types, that is, black raspberries (BRBs), strawberries (STRWs), and blueberries (BBs), that differ in their content of ellagitannins in the order BRB > STRW > BB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…BB contains five distinct anthocyanidins (Dp, Cy, Pt, Pe, and Mv) where as BRB contains almost exclusively Cy and EA. However, the role of the fibers from BB and BRB in tumor inhibitory activity cannot be completely ruled out as fiber fraction from three different berries have been shown to possess chemoprevention activity against esophageal tumorigenesis [6].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…BB contains five distinct anthocyanidins (Dp, Cy, Pt, Pe, and Mv) where as BRB contains almost exclusively Cy and EA. However, the role of the fibers from BB and BRB in tumor inhibitory activity cannot be completely ruled out as fiber fraction from three different berries have been shown to possess chemoprevention activity against esophageal tumorigenesis [6].…”
Section: Resultsmentioning
confidence: 99%
“…Berries have received great attention lately based on their potential to prevent chemically-induced colon [3] and esophageal [4] cancers in animal models. The initial evidence that berry anthocyanins are chemopreventive in an animal tumor-model was provided by Wang et al [5,6]. This study also demonstrated that the anthocyanin fraction of black raspberries (BRB) was as effective in preventing chemically-induced esophageal tumors in rats as whole BRB powder [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants rich in ellagitannins may prevent or delay the lengthy carcinogenesis process ]. Ellagitannins and ellagic acid inhibit cancers of the mouth, esophagus, lung, breast, liver and colon [Aqil et al 2012, González-Sarrías et al 2013a, b, Sakagami et al 2000, Wang et al 2010, 2013.…”
Section: Antitumor Activity Of Ellagitanninsmentioning
confidence: 99%